Тема як компонент актуального членування простого речення: структура, семантика, засоби експлікації - Костусяк, Наталія Миколаївна (My University, 2016)
In this article a theme as a component of simple syntax constructions in the story “Lake wind” of J. Pokalchuk is analyzed. The accent falls on the peculiarities of its expression, its ratio with components of the formal syntactic and semantic organization. It was found that simple theme often correlates with subjects, which have different structure. Peripheral formal expressions are lexems related with controlled parts of sentence and determinants. Complicated theme usually marks a subject and subordinated coordinated and uncoordinated attribute, less – determinants and locatives, which valence is associated with predicate. Theme with several degrees rarely happens in the research.
Keywords: theme; actual segmentation; the subject; controlled part of the sentence; attribute